Precision-engineering of subunit vaccine particles for prevention of infectious diseases - Chen, Shuxiong; Pounraj, Saranya; Sivakumaran, Nivethika; Kakkanat, Anjali; Sam, Gayathri; Kabir, Md. Tanvir; Rehm, Bernd H. A. (Frontiers in Immunology, 2023)
Vaccines remain the best approach for the prevention of infectious diseases. Protein subunit vaccines are safe compared to live-attenuated whole cell vaccines but often show reduced immunogenicity. Subunit vaccines in particulate format show improved vaccine efficacy by inducing strong immune responses leading to protective immunity against the respective pathogens. Antigens with proper conformation and function are often required to induce functional immune responses. Production of such antigens requiring post-translational modifications and/or are composed of multiple more complex domains in bacterial hosts remains challenging. Here, we discuss strategies to overcome these limitations toward the development of particulate vaccines eliciting desired humoral and cellular immune responses. We also describe innovative concepts of assembling particulate vaccine candidates with complex antigens bearing multiple post-translational modifications. The approaches include non-covalent attachments (e.g. biotin-avidin affinity) and covalent attachments (e.g. SpyCatcher-SpyTag) to attach post-translationally modified antigens to particles.